PERHITUNGAN HARGA POKOK PRODUKSI KERUPUK DENGAN MENGGUNAKAN METODE FULL COSTING (Studi Kasus Pada UKM Kerupuk Cita Rasa Sidomulyo Barat – Pekanbaru) - Fifitri Ali; Annisha Harianti (AkMen JURNAL ILMIAH, 2020)
This research was conducted to determine the calculation the cost of goods manufactured using the full costing method and to find out the difference in the calculation of the cost of goods manufactured based on UKM Kerupuk Cita Rasa. After calculating the cost of goods manufactured using the full costing method, there is a difference with the calculations made by the UKM. The difference in the calculation of the cost of goods manufactured based on the UKM using the full costing method per product unit is Rp 9.90 for Palembang crackers and Rp 3.42 for rice crackers. Meanwhile, the overall difference between the calculation based on UKM and the calculation using the full costing method is Rp 13.32 per product unit. This is because the imposition of more detailed overhead costs for each product. The calculation of the cost of goods manufactured according to the company does not separate the cost of goods manufactured per product, while the calculation of the cost of goods manufactured using the full costing method separates the cost of goods manufactured for each product. Keywords : Cost of Goods Manufactured, Full Costing, Overhead Cost